Challenges in diagnosis in couple and family systems work - Asfaw, Amanuel Haile; Warren, Jane; Zakaria, Noor Syamilah (Sage Publications, 2019)
Choosing to use a formal diagnosis in couples and family counseling can be a treatment conundrum for counselors who believe they must provide a diagnosis. To create a diagnosis for financial reimbursement is a fraudulent and an unethical practice. This article addresses diagnosis in couples and family work and offers strategies to use when not diagnosing.